Analisa dan Perancangan Sistem Informasi Aktiva Tetap dalam Upaya Pengendalian aktiva Tetap yang Bersumber dari Pembelian dan Donasi - Eka Novianti (Bina Nusantara University, 2011)
In an institution of capital assets is one of the very important work that needs to be managed well, both in terms of maximizing the value of benefits and terms of existence that can be used optimally. Likewise, management information about the assets that will be used for good decision-making. A system designed to optimally utilize the information. Fixed Assets Information System that meets the user requirements and works properly can provide precise and accurate information is required. Users can easily find out the value of the acquisition and the value of accumulated depreciation of assets which no longer belongs to the company. The values that have an impact on the Financial Position Report will generate a report more accurate and reliable.